Pension Systems in Sub-Saharan Africa : Brief Review of Design Parameters and Key Performance Indicators - Abels, Miglena; Guven, Melis U. (2016)
The paper summarizes key design characteristics and performance indicators of national and civil service pension schemes in Sub-Saharan Africa (SSA). It is intended to serve as a resource in pension reform efforts in the region. The note delivers an up-to date assessment of the main design parameters, key performance metrics, and main challenges facing pension systems in SSA. The information provided in the note aims to capture current trends in the region and benchmark performance and pension system design choices made by countries against international experience. Section one provides an overview of mandatory national pension systems in the region whereas Section two presents the key design features of civil service pension schemes. Section three analyzes the performance of both national and civil service pension schemes; particular attention is paid to the fiscal performance and equity of the pension schemes. Pension system design parameters of both national and civil service pension schemes are discussed in section four. Section five aims to enhance the paper by providing relevant demographic data and analysis.